Manifestly covariant actions for D=4 self-dual Yang-Mills and D=10 super-Yang-Mills - Berkovits, N.; Hull, C. (Editrice Compositori Bologna, 1998)
Using an infinite number of fields, we construct actions for D = 4 self-dual Yang-Mills with manifest Lorentz invariance and for D = 10 super-Yang-Mills with manifest super-Poincare invariance. These actions are generalizations of the covariant action for the D = 2 chiral boson which was first studied by McClain, Wu, Yu and Wotzasek.
Keywords: field theories in higher dimensions; duality in gauge field theories; extended supersymmetry; supersymmetry and duality